Early-life nutrition and adult-life outcomes - João Guilherme Bezerra Alves; Lucas Victor Alves (Elsevier, 2024)
Objectives: To verify the association between early-life nutrition and chronic adult diseases. Data Sources: Medline, Embase, Cochrane Database, and Lilacs. Summary of finds: The Developmental Origins of Health and Disease (DOHaD) hypothesis postulates that a mismatch between early-life circumstances and later-life situations may have an impact on chronic diseases. In this review, the authors emphasize the research supporting the impact of early nutrition on the origins of adult height, obesity and metabolic syndrome, type 2 diabetes mellitus, cardiovascular diseases, and reproductive outcomes. Conclusion: Even though this is a new topic and there are still many research questions to be answered, there is strong evidence that both deficiency and excess nutrition in early life can cause epigenetic changes that have effects that last a lifetime and contribute to the development of chronic diseases. Public health efforts to protect adults from getting chronic diseases should focus on nutrition in the first 1000 days of life, from conception to the end of the second year of life.